Cooling Period Calculation of Evolutionary Power Reactor Spent Fuel for Dry Management Safety - Youssef, M.I.; Sultan, G.F.; Morsi, H.F. (Ядерна та радіаційна безпека, 2016)
The calculation of the evolutionary power reactor (EPR) spent fuel (SF) cooling period (CP) was performed. The CP was determined by comparing the heat load of a cask with the calculated value of EPR decay heat (DH). The EPR DH was calculated by the ORIGEN computer code based on the EPR parameters. For conservatively study, the EPR and ORIGEN parameters that lead to higher DH values were selected and safety margins were considered. The fitting tool was utilized in the calculation of CP to overcome the ORIGEN limitation. The resultant values of CP will maintain the peak cladding temperature (PCT) of SF lower than 400°C during storage, transport, and disposal. The results show that -for normal operation- the SF of EPR should stay in the pool at least 4.75 years before it is loaded to the passively cooled dry casks. Выполнен расчет периода охлаждения отработавшего ядерного топлива эволюционного(европейского) энергетического реактора (ЭЭР). Период охлаждения определялся путем сравнения термической нагрузки на контейнер с вычисленным значением остаточного энерговыделения ЭЭР. Остаточное энерговыделение ЭЭР рассчитано с применением компьютерного кода ORIGEN на основании параметров ЭЭР. Для консервативного анализа выбраны такие параметры ЭЭР и ORIGEN, которые приводят к более высоким значениям остаточного энерговыделения, а также обеспечивают необходимые запасы безопасности. При расчете периода охлаждения применялась методика корректировки для преодоления ограничения кода ORIGEN. Полученные значения периода охлаждения обеспечат поддержание максимальной температуры оболочек твэлов отработавшего топлива на уровне ниже 400 °C при хранении, транспортировке и захоронении. Результаты показали, что для нормальной эксплуатации отработавшее топливо ЭЭР должно оставаться в бассейне выдержки как минимум 4,75 года перед загрузкой в контейнеры сухого хранения с пассивным охлаждением. Розраховано період охолодження відпрацьованого ядерного палива (ВЯП) еволюційного (європейського) енергетичного реактора (ЕЕР). Період охолодження визначався порівнянням термічного навантаження на контейнер зберігання з обчисленим за допомогою комп’ютерного коду ORIGEN на основі параметрів ЕЕР значенням остаточного енерговиділення ЕЕР. Для консервативного аналізу обрано такі параметри ЕЕР та ORIGEN, що призводять до більш високих значень остаточного енерговиділення, а також забезпечують потрібні запаси безпеки. У розрахунку застосовано методику коригування для подолання обмеження коду ORIGEN. Отримані значення періоду охолодження забезпечать підтримку максимальної температури оболонок твелів ВЯП на рівні нижчому, ніж 400 °C, протягом зберігання, транспортування та захоронення. Результати показали, що ВЯП для нормальної експлуатації має залишатись у басейні витримки принаймні 4,75 року перед завантаженням у контейнери сухого зберігання з пасивним охолодженням.